2019
DOI: 10.1111/jcmm.14364
|View full text |Cite
|
Sign up to set email alerts
|

Pigment epithelium‐derived factor peptide promotes limbal stem cell proliferation through hedgehog pathway

Abstract: Expansion of limbal epithelial stem cells (LSCs) is crucial for the success of limbal transplantation. Previous studies showed that pigment epithelium‐derived peptide (PEDF) short peptide 44‐mer could effectively expand LSCs and maintain them in a stem‐cell state, but the mechanism remained unclear. In the current study, we found that pharmacological inhibition of Sonic Hedgehog (SHh) activity reduced the LSC holoclone number and suppressed LSC proliferation in response to 44‐mer. In mice subjected to focal li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
(113 reference statements)
0
15
0
Order By: Relevance
“… 1 Cyclin D1 is a well-known cell cycle regulator and a transcriptional target of the Hippo-Yap signaling pathway, 47 which is also a key factor in regulating limbal stem cell proliferation. 48 Our study proved Agrin could inhibit the phosphorylation of Yap1 and modulate the expression of downstream Cyclin D1, which further activating limbal stem cell proliferation.…”
Section: Discussionmentioning
confidence: 58%
“… 1 Cyclin D1 is a well-known cell cycle regulator and a transcriptional target of the Hippo-Yap signaling pathway, 47 which is also a key factor in regulating limbal stem cell proliferation. 48 Our study proved Agrin could inhibit the phosphorylation of Yap1 and modulate the expression of downstream Cyclin D1, which further activating limbal stem cell proliferation.…”
Section: Discussionmentioning
confidence: 58%
“…Growth factors are key components for the development and function of the limbal niche and accumulating evidence suggested that they play important roles in regulating LESCs survival and development 22,38,41‐46 . In addition, as shown above, LNCs act in a paracrine fashion to support LESCs in vitro, and so, we decided to analyse whether SOX10 acts through growth factors to influence the survival of LESCs in LNCs.…”
Section: Resultsmentioning
confidence: 99%
“…that they play important roles in regulating LESCs survival and development. 22,38,[41][42][43][44][45][46] In addition, as shown above, LNCs act in a paracrine fashion to support LESCs in vitro, and so, we decided to analyse whether SOX10 acts through growth factors to influence the survival of LESCs in LNCs. To identify which factors might be involved, we compared the expression of a series of growth factor genes in si-Sox10 transfected LNCs vs si-C or mock-transfected LNCs.…”
Section: Sox10 Controls the Ability Of Lncs To Serve As A Niche Formentioning
confidence: 99%
“…In addition, integrated RNA-seq and proteomic pathway analyses revealed changes in Hedgehog signaling and TGF-β ( Figure 3 C). Study of Hedgehog in mice indicates that it may play a role in both corneal epithelial regeneration and limbal epithelial maintenance [ 49 , 50 , 51 ]. TGF-β regulates several essential cellular processes in the cornea, such as local inflammatory responses and wound healing in ocular surface epithelial cells [ 52 ].…”
Section: Discussionmentioning
confidence: 99%